Factors of Political Participation of Beginner Voters Not Using Their Voting Rights in Elections in West Java - Fajarwati, Arnia; Anzani, Elvira Aprilla; Susanti, Dian; Muhtadi, Alfian Ali; Annisa, Annisa; Nuryani, Elin; Gania, Gema Sunda; Faisa, Khailla Tavania; Gunardie, Muhammad Luthfi; Sophiana, Risa (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
This study aims to examine the factors that influence the political participation of novice voters not using their voting rights in elections in West Java. The method used in this research is to use a qualitative approach, namely the descriptive method. This research will provide an opportunity for subjects (first-time voters) to answer the questions asked according to their own experiences, and not based on the benchmark answers that have been made by researchers. This means that first-time voters behave and act in such a way as to feel free to use their knowledge and experience of the topics offered. The conclusion of this research is that there are several factors that encourage students of Langlangbuana University to use their voting rights during elections. Some of the factors found are factors of political stimulation, in order to realize the importance of using voting rights. Then the second factor is the factor of the characteristics of the person, because those with a social character who have great social concern for social, political, economic, socio-cultural, and defense problems, usually want to be involved in political activities. The third is the factor of the social environment, and the last is the factor of political education that novice voters get. Most of the students of Langlangbuana University already have care and awareness about the importance of their voting rights in the election, and have desires and hopes for the people they will choose as leaders in this country.